1999
DOI: 10.1042/bj3400309
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of glutathione S-transferase isoforms in the seminiferous tubular fluid, tissue distribution and sex steroid binding by rat GSTM1

Abstract: The seminiferous tubular fluid (STF) provides the microenvironment necessary for spermatogenesis in the adluminal compartment of the seminiferous tubule (ST), primarily through secretions of the Sertoli cell. Earlier studies from this laboratory demonstrated the presence of glutathione S-transferase (GST) in STF collected from adult rat testis and in the spent media of ST cultures. This study describes the cellular source, isoform composition and possible function of GSTs in the STF. The major GST isoforms pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…It was found in the present cDNA microarray analysis that the gene expression of Sertoli-germ cells adhesion molecules such as cadherin (Johnson et al, 2000), fibronectin (Schaller et al, 1993), and integrin (Siu et al, 2003) was decreased in the 2,5-HD high-dose group. Furthermore, the genes that are expressed in Sertoli cells such as IGFBP-3 (Smith et al, 1990), ferritin (Carreau, 1996), epidermal growth factor receptor (Suarez-Quian et al, 1994) and GST-pi (Mukherjee et al, 1999) were altered. Expression changes of these genes might underlie the toxicity of 2,5-HD observed in Sertoli cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found in the present cDNA microarray analysis that the gene expression of Sertoli-germ cells adhesion molecules such as cadherin (Johnson et al, 2000), fibronectin (Schaller et al, 1993), and integrin (Siu et al, 2003) was decreased in the 2,5-HD high-dose group. Furthermore, the genes that are expressed in Sertoli cells such as IGFBP-3 (Smith et al, 1990), ferritin (Carreau, 1996), epidermal growth factor receptor (Suarez-Quian et al, 1994) and GST-pi (Mukherjee et al, 1999) were altered. Expression changes of these genes might underlie the toxicity of 2,5-HD observed in Sertoli cells.…”
Section: Discussionmentioning
confidence: 99%
“…HSP70-2 is a molecular chaperon for meiosis in spermatogenesis and knockout mice lacking this gene are infertile (Eddy, 1999). GST-pi is contained in seminiferous tubular fluid (Aravinda et al, 1995), and this fluid provides the microenvironment necessary for spermatogenesis (Mukherjee, et al, 1999). Therefore, alterations of the expression of these molecules may lead to anomalous spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Different glutathione-S-transferases (GSTs) isoforms are present in the testes, epididymides, and spermatozoa from different mammalian species, including humans, goats, boars, buffalos, and rodents (Veri et al 1993, Gopalakrishnan et al 1998, Mukherjee et al 1999, Raijmakers et al 2003, Kumar et al 2014, Llavanera et al 2020. GSTs are being discovered as crucial elements in the antioxidant response to sustain male fertility.…”
Section: Glutathione-s-transferasesmentioning
confidence: 99%
“…In the present study, 28GST was shown to be localized most densely in sperm tails of of C. sinensis. Isoform of class Mu GST is present in human testes (Hussey and Hayes, 1993) and abundant in fluid of seminiferous tubules of rat testes (Mukherjee et al, 1999). Sertoli cells are prime secretors of Mu GSTs in rat testes.…”
Section: Discussionmentioning
confidence: 98%